Firm Characteristics and Management Performance: A Governance-Based Assessment of Indonesian SOEs - Dewi Sutjahyani (Journal of Economics, Business, and Government Challenges, 2025)
This study investigates the influence of ownership structure, capital structure, and firm characteristics on management performance in Indonesian State-Owned Enterprises (SOEs), with Good Corporate Governance (GCG) examined as a moderating variable. Using a quantitative associative approach and Moderated Regression Analysis (MRA) within the PLS-SEM framework, the research analyzes data from 10 SOEs listed on the Indonesia Stock Exchange between 2021 and 2024. The findings reveal that only firm characteristics—specifically firm size and age—significantly enhance management performance, while ownership structure and capital structure show no significant effects. Additionally, GCG demonstrates neither a direct influence nor a moderating role in the tested relationships. The novelty of this study lies in its empirical focus on newly listed SOEs during a critical period of governance reform, offering fresh insights into the symbolic implementation of GCG and its limited impact on managerial outcomes. These results contribute to the growing body of literature on public enterprise governance by highlighting the importance of internal organizational capacity over structural and regulatory compliance. The study suggests that future reforms in SOEs should prioritize institutional strengthening and capacity-building to achieve effective governance and sustainable performance.